Leadership Strategies of School Principals in Enhancing Quality Education in the Era Of Freedom to Learn - Paulus Joseph Mentang; Fabiola Wawuo; Nazarius S (STAI Miftahul Ula Nganjuk, 2024)
As a leader, the school principal faces significant challenges in developing school quality standards. The principal must plan appropriate programs and strategies to improve the quality of the school, achieve academic excellence, and produce graduates ready to compete globally. The aim of this research is to describe (1) the strategies implemented by the school principal in enhancing school quality, (2) the impact of the implementation of these programs and strategies, and (3) the supporting and hindering factors in their implementation. This research adopts a field study approach with a qualitative and descriptive methodology, employing interview techniques, observations, and document analysis. The primary informants for this research are school principals and teaching staff. The research findings indicate that the programs implemented by the school principal to enhance school quality include curriculum development, improvement of teacher quality, focus on student needs, and enhancement of school facilities. The strategies implemented by the school principal have proven successful and have a positive impact on raising school standards. The implementation of these programs and strategies is tailored to the specific needs of the school. The positive impact of the programs and the leadership of the school principal is reflected in the achieved excellence, both academically and extracurricularly. Factors supporting the school's success have been effectively managed by the school principal.